Impacts of Aircraft Noise on Psychosocial Health of Man: A Study in Sam Mbakwe International Cargo Airport, Imo State, Nigeria - , Chidinma Acholonu, Diagi E. Bridget, Chukwudi Nwaogu, Justin N. Okorondu, Ekweogu Chinonye, Ajiere Susan, Agidi Victor, Chijioke Uyo, Obijuru Ifeoma (Archives of Current Research International, 2024)
Noise can be seen as unwanted sound which is unpleasant to man and the Environment. One of the sources of noise pollution which has effect on man is aircraft noise. Noise assessment level data were obtained at three stages of aircraft operation; Standby, Take-off and Landing for a period of five days. Two airlines within the same age limit were assessed for the study. The sound meter utilized in this study is sound meter android application. It has the measurement range of 30 to 130 dB(A) with an accuracy of ±2 dB(A) and resolution 0.1 dB(A). 100 copies of structured questionnaire were used to solicit information within the airport environment from workers on the perceived effects of aircraft noise on their health and daily activities within the airport. Data were collected and compared with World Health Organization (W.H.O) standard. Findings of the study revealed that the recorded noise levels were above the W.H.O permissible limit. Although, there were variation in noise level between the two airlines and the different stages assessed. Findings from the questionnaire survey also revealed that 80% of the population admitted that the noise levels had impact on their health ranging from annoyance, stress, deprivation of sleep, hearing problems amongst others. The study confirmed that aircraft noise had an impact on health and well-being of people. The study therefore, recommends that there is need to reduce the aviation noise impacts in other to promote human and environmental health.